PEMBUATAN DAN UJI ORGANOLEPTIK SEDIAAN TEH CELUP DAUN AFRIKA (Vernonia amygdalina Del.) MELALUI METODE PENGOVENAN DAN METODE SINAR MATAHARI - Novitasari, Reta; Ratnasari, Dewi; Nuraini, Siti Sarah (Sekolah Tinggi Ilmu Kesehatan Holistik, 2018)
Background: African leaves are one of the medicinal plants that are effective for treating diabetes. Syrup preparations from African leaves only lasted less than 2 weeks, so in this study African leaves were made in the form of teabags which were made by comparing between oven and sunshine methods. Objective: This study aims to reduce blood glucose levels through the oven and sunshine method. Method: This research uses action research research design, observation of organoleptic test and shrinkage of preparation for 3 weeks. Result: The results of the study obtained an average percentage of drying losses with the oven method which is 2.3% and the average percentage by the sunshine method is 6%. For organoptic test observations on the 21st day the samples with the oven oven method were dark green, smelled of ginger, bitter taste, coarse powder form. Whereas for samples with pale green sunlight method, there is no smell of ginger, bitter taste and preparations in the form of coarse powder. Conclusion: From the results of the study concluded that the preparation of preparations using the oven method is relatively better. It is recommended to conduct further research to test the effectiveness and preference for this African leaf tea bag.